The Application of Data Mining Techniques in Agricultural Science - Fetanat, Hooman; Mortazavifar, Leila; Zarshenas, Narsis (Ciência e Natura, 2015)
Information Technology has a positive impact on other disciplines. Using today's technology, precision agriculture and InformationTechnology are mixed together. Use of Information Technology in agriculture will lead to improvements in productivity. For this purpose,the raw data is transformed into useful information through data mining. This research determined whether data mining techniques can alsobe used to improve pattern recognition and analysis of large growth factors of ornamental plants experimental datasets. Furthermore, theresearch aimed to establish data mining techniques can be used to assist in the classification and regression methods by determining whethermeaningful patterns exist various growth factors of ornamental plants characterized at various research sites across Kish Island. Differentdata mining techniques were used analyze a large data base of ornamental plants properties attributes. The data base has been collected fromdifferent plants of Kish Island in various areas in order to determine, classify and predict effective growth factors on blooming. In thisresearch, analyzed data with regression technique showed the effect of chlorophyll content on the number of flowers. The analysis of theseagricultural data base with different data mining methods may have some advantages in agriculture